TRANSFORMASI SOSIAL-BUDAYA KOMUNITAS ADAT SADE DALAM PUSARAN ARUS PANDEMI COVID-19 DAN PARIWISATA - Saharudin Saharudin; Sukri Sukri; Pahrudin Arrozi (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2021)
This study was aimed at investigating how the Sade indigenous communities in Lombok carried out their socio-cultural transformation (especially during the Covid-19 pandemic). Specifically, this study sought for evidence of how the communities balanced the demands of tourism industry while preserving the local culture during the Covid-19 pandemic. Transformation theory was employed to examine the balance, involving an analysis of the dialectical process in the community during which the mediation of anxiety and calmness occurred to achieve certain objectives. The data were collected through interview and participant observation. The study revealed the socio-cultural transformation of the Sade-Lombok indigenous community during the Covid-19 pandemic was in form of community’s creativities and reforms in accommodating particular changes caused by the pandemic and modifying particular community rituals. The accommodation and modification were reinforced by the demands of the government, tourism agency and/or economic needs. Therefore, the study concluded that the socio-cultural transformation of the Sade-Lombok indigenous community during the Covid-19 pandemic was achieved through dialectical processes between anxiety and calmness resulted in the preservation of the local traditions, creativity, and reforms.